A member of the ALOG gene family has a novel role in regulating nodulation in Lotus japonicus. Issue 4 (12th November 2018) - Lei, Yawen; Su, Shihao; He, Liang; Hu, Xiaohe; Luo, Da
Abstract: Legumes can control the number of symbiotic nodules that form on their roots, thus balancing nitrogen assimilation and energy consumption. Two major pathways participate in nodulation: the Nod factor (NF) signaling pathway which involves recognition of rhizobial bacteria by root cells and promotion of nodulation, and the autoregulation of nodulation (AON) pathway which involves long‐distance negative feedback between roots and shoots. Although a handful of genes have a clear role in the maintenance of nodule number, additional unknown factors may also be involved in this process. Here, we identify a novel function for a Lotus japonicus ALOG ( A rabidopsisL SH1 and O ryzaG 1) family member, LjALOG1, involved in positively regulating nodulation. LjALOG1 expression increased substantially after inoculation with rhizobia, with high levels of expression in whole nodule primordia and in the base of developing nodules. The ljalog1 mutants, which have an insertion of the LORE1 retroelement in LjALOG1, had significantly fewer nodules compared with wild type, along with increased expression of LjCLE‐RS1 ( L. japonicus CLE Root Signal 1 ), which encodes a nodulation suppressor in the AON pathway. In summary, our findings identified a novel factor that participates in controlling nodulation, possibly by suppressing the AON pathway. Abstract : Nodule is a specialized organ on the roots that can fix atmospheric nitrogen. In this study, we identified a novel function for LjALOG1 in positively regulating nodulation in Lotus japonicas . LjALOG1 is highly expressed in nodules and its mutant results in significantly decreased nodules number.